APPLICATION OF FOREST PATHOLOGY MONITORING SPATIAL DATABASE FOR FOREST CONDITION ASSESSMENT - Eydlina, S. P.; Knyazeva, S. V. (InterCarto. InterGIS, 2015)
Currently the largest project of monitoring forest condition in the world is the international UN/ECE ICP Forests program involving 41 countries. The program is developed on the basis of The Convention on long-range transboundary air pollution. In accordance with the Convention on long-range transboundary air pollution (CLRTAP UNECE) 1985 and 1987 under the terms of the agreement, the monitoring of the ICP Forests program should be undertaken in the following subjects of the Russian Federation: The Republic of Karelia, Leningrad oblast, Murmansk oblast; Novgorod oblast, Pskov Oblast, Kaliningrad oblast. In Russian national center of ICP Forests monitoring it was created the ICP Forests Spatial Database (ICP Forests SDB) for the North-Western territory of the Russian Federation. The article discusses the results of the monitoring carried out in accordance with the standards of the program.